P14.72 Multicentric glioblastoma - A retrospective study of imaging characteristics, treatment approach, pattern of relapse and survival - Benouaich Amiel, A (Neuro Oncol, 2019)
BACKGROUND: Multicentric glioblastoma (m-GBM), defined as well separated tumoral foci, is a rare GBM variant comprising 6–13% of all GBM cases. Published data regarding m-GBM is scarce and is largely reporting on multicentric enhancing foci. We performed a retrospective study to determine the incidence, imaging characteristics, treatment approach, pattern of relapse and prognosis of m-GBM. MATERIAL AND METHODS: The neuropathological database of our institution was surveyed for histological diagnosis of adult GBM diagnosed between 01/01/2015 and 31/05/2018. All pre-operative MRI were reviewed to identify patients with m-GBM. We included in the definition of m-GBM well separated enhancing as well as non-enhancing tumor foci. The medical records and follow-up MRI studies were reviewed in order to retrieve the data. RESULTS: Of the 170 patients with newly diagnosed GBM 14 (8%) presented with m-GBM. All of them had at least one enhancing lesion and 11 (78.5%) patients had additional well separated non-enhancing tumor foci. The total number of lesions was 37 (19 enhancing and 18 non-enhancing) with a median number of lesions per patient of 2 (range 2 to 4). Median age at diagnosis was 66 (range: 49–79) years. Nine of the patients (64%) underwent surgical resection of the enhancing component whereas 5 patients had only a biopsy. Median follow up was 14.3 (range: 2–30) months. All but one patients were treated by standard concurrent radiotherapy with temozolomide. Median progression free survival is 6.2 (range: 0–13.3) months. Five of the 18 non-enhancing tumor foci eventually displayed contrast enhancement during the course of the disease. At last follow up, 12 patients died, with an overall survival of 12.3 months. Information regarding radiation fields, pattern of disease progression and molecular profile will be presented at the meeting. CONCLUSION: m-GBM presents therapeutic dilemas regarding the optimal surgical approach and radiation field planning. Better understanding of the disease course and pattern of progression may help to optimize the therapeutic approach implying particularly to non-enhancing tumor foci.